The Evaluasi Kelayakan Pembangunan Rumah Sederhana Program Bantuan Stimulan Perumahan Swadaya: - - Ernawati, Ernawati; Latupeirissa, Josefine Ernestine; Bungin, Erni Rante (JURNAL SIMETRIK, 2025)
The need for housing is increasing in line with population of Indonesia. Therefore, housing development needs to be encouraged for the sustainability of housing availability for the people, including Low-Income Communities. The construction of Simple Houses under the Bantuan Stimulan Perumahan Swadaya Program (BSPS) in Village "B" in Ambon City needs to be evaluated for its feasibility to ensure compliance with applicable standards. Therefore, the purpose of this study is to evaluate the feasibility of new construction of simple houses under the BSPS program at that location. Observation and distribution of questionnaires were carried out to collect primary data while secondary data were in the form of documents, where both data were obtained from related parties. The MLR method was used to analyze the effect of three independent variables, i.e. the adequacy of the area of the house building (X1), the safety of the house building (X2), and the health of the occupants/house building (X3) on the dependent variable, habitable houses (Y). The results that the independent variables X1, X2, and X3 had a positive effect on the dependent variable Y, which means that the Construction of Simple Houses under the BSPS in Village "B" in Ambon City is feasible. Keywords: Evaluation, housing feasibility, minimalist house development, BSPS programme